ANALISIS PERENCANAAN DAN PENGANGGARAN PENDIDIKAN DI SMA UNGGUL DEL - Zandroto, Weni; Daryanto, Eka; Restu, Restu (Dharmas Education Journal (DE_Journal), 2024)
This research aims to analyze educational planning and budgeting at Unggul Del High School. Using a qualitative approach, data was collected through in-depth interviews with school principals, direct observation of school activities, and analysis of documents related to the School Revenue and Expenditure Budget Plan (RAPBS). The research sample consisted of school principals, deputy principals, and teachers, who were selected based on their involvement in the planning and budgeting process. The results of the research show that educational planning and budgeting in the form of the Del Superior High School program went according to plan and was effective, focusing on: First; Curriculum Innovation successfully integrates the Independent Curriculum and the international Curriculum to create a flexible learning environment that meets international standards. Second, developing the competence of teachers and students through training and olympiads, showing significant academic achievements in learning outcomes and national to international olympiads. Third, strengthening the SPMI team through cadre of work teams, thus ensuring the quality of education is maintained. These findings confirm SMA Unggul Del’s commitment to providing high-quality education and supporting teachers and students to reach their full potential at a global level.